Optical and electronic logic gate with orthogonal inputs - Xu, Cai (2018)
Logic gate is the fundamental for computational operation. With the fast development of information technology, it is necessary to develop the logic operation system at micro or nanoscale. At the meantime exploring different kinds of output signal and incorporating various inputs could significantly extend the potential application of logic gate.